New-onset refractory status epilepticus (NORSE) in a 23-year-old female. (December 2020) - Morrison, H.D.; Morgan, C.; Urankar, K.; Wylde, J.; O'Beirne, M.; Krolikowski, K.; Wakerley, B.R.
Highlights: Mitochondrial disease is a rare cause of new-onset refractory status epilepticus (NORSE). We present a case NORSE caused by POLG-related mitochondrial disease. This case is illustrated with MRI brain and EEG typical of POLG.